Factors associated to endodontically treated tooth survival in patients over 20 years of age seen in a private IPS between 2006 and 2012 - Pineda-Vélez, Eliana; Segura-Cardona, Ángela María (Revista Facultad de Odontología Universidad de Antioquia, 2014)
Introduction: endodontics is the branch of dentistry that studies the morphology, function, and alterations of the dental pulp and periodontal region, as well as their treatment. Success rates in endodontics are usually high but survival has not been thoroughly studied. The objective of this study was to determine survival time and clinical and demographic factors influencing endodontically treated teeth loss. Methods: this was a cohort follow-up study with survival analysis in order to assess the status of endodontically treated teeth based on systematic collection of information obtained from medical records. Results: we found a population with low income and with technical or vocational education; males were predominant in this population. Extraction or tooth loss occurred earlier in males, and even earlier in those with lower income and apical lesions larger than 11 mm. Conclusion: having a tooth with an apical lesion larger than 11 mm significantly explains earlier dental loss.